Green Accounting and Sustainable Performance of Micro, Small, and Medium Enterprises: The Role of Financial Performance as Mediation - Maya Indriastuti; Mutamimah (The Indonesian Journal of Accounting Research)
The performance of Micro, Small, and Medium Enterprises (MSMEs) has become a top priority in all countries due to a global perspective recognizing MSMEs as a tool for economic growth. Therefore, MSMEs must be able to choose strategies to enhance their financial performance towards a sustainable business, one of which is implementing a green accounting strategy. This research aims to explore financial performance's role in mediating green accounting's effect on sustainable performance. Questionnaires were distributed to 420 MSMEs owners in Central Java via the Google form. From the 420 questionnaires, 405 were then analyzed using SmartPLS. The study results show that the sustainable performance of MSMEs can be improved through green accounting and financial performance. In addition, concern for MSMEs towards the environment through green accounting can be an added value for MSMEs businesses in Central Java, Indonesia.